2023
DOI: 10.1107/s2056989023002098
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and structure of 4-hydroxy-N-isopropyltryptamine (4-HO-NiPT) and its precursors

Abstract: The title compound, 4-hydroxy-N-isopropyltryptamine (4) or 4-HO-NiPT (systematic name: 3-{2-[(propan-2-yl)amino]ethyl}-1H-indol-4-ol), C13H18N2O, was synthesized in three steps from 4-benzyloxyindole (1) (systematic name: 4-phenoxy-1H-indole), C15H13NO. (1) was treated with oxalyl chloride and isopropylamine to produce N-isopropyl-4-benzyloxy-3-indoleglyoxylamide (2) {systematic name: 2-[4-(benzyloxy)-1H-indol-3-yl]-2-oxo-N-(propan-2-yl)acetamide}, C20H20N2O3. (2) was reduced to generate 4-benzyloxy-N-isopropy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…This includes the zwitterionic natural product baeocystin (Naeem, Sherwood et al, 2022), its metabolite norpsilocin as both its freebase and fumarate (Chadeayne et al, 2020b), and its synthetic prodrug 4-acetoxy-N-methyltryptamine as a chloride salt (Glatfelter et al, 2022b). The remaining three are N-methylserotonin hydrogen oxalate (Naeem, Anas et al, 2023), 4-benzyloxy-N-isopropyltryptammonium chloride and 4-hydroxy-N-isopropyltryptamine (Laban et al, 2023) There are only four structures of freebase tryptamines known without indole substitution: the natural products tryptamine (Nowell et al, 2002) and N,N-dimethyltryptamine (Falkenberg, 1972), as well as N-methyl-N-propyltryptamine (Chadeayne et al, 2019b), and 3-[2-(piperidin-1-yl)ethyl]-1Hindole (Sahoo et al, 2020), while many other tryptamine freebases have been reported including serotonin .…”
Section: Database Surveymentioning
confidence: 99%
“…This includes the zwitterionic natural product baeocystin (Naeem, Sherwood et al, 2022), its metabolite norpsilocin as both its freebase and fumarate (Chadeayne et al, 2020b), and its synthetic prodrug 4-acetoxy-N-methyltryptamine as a chloride salt (Glatfelter et al, 2022b). The remaining three are N-methylserotonin hydrogen oxalate (Naeem, Anas et al, 2023), 4-benzyloxy-N-isopropyltryptammonium chloride and 4-hydroxy-N-isopropyltryptamine (Laban et al, 2023) There are only four structures of freebase tryptamines known without indole substitution: the natural products tryptamine (Nowell et al, 2002) and N,N-dimethyltryptamine (Falkenberg, 1972), as well as N-methyl-N-propyltryptamine (Chadeayne et al, 2019b), and 3-[2-(piperidin-1-yl)ethyl]-1Hindole (Sahoo et al, 2020), while many other tryptamine freebases have been reported including serotonin .…”
Section: Database Surveymentioning
confidence: 99%